The rehabilitation including structured active play (RePlay) model: A conceptual model for organizing physical rehabilitation sessions based on structured active play for preschoolers with cancer - Pouplier, Anna; Larsen, Hanne Baekgaard; Christensen, Jan; Schmidt-Andersen, Peter; Winther, Helle; Fridh, Martin Kaj (Frontiers in Pediatrics, 2022)
Anti-cancer treatments, as well as cancer itself, reduces children’s cardiorespiratory fitness, muscle strength, and gross motor functions. Early rehabilitation programs, including physical activity for childhood cancer patients, can counteract these adverse treatment effects. Previous studies of school-aged children (6‒18 years old) indicate that physical activity, including aerobic and resistance training, is safe, feasible, and effective. The goal of structured physical activity rehabilitation for preschool children (1‒5 years old) is to support gross motor development and opportunities to move freely in various ways. Specific rehabilitation for preschoolers diagnosed with cancer is needed to promote physical-, social-, and personal development. This paper introduces a conceptual model—The RePlay (Rehabilitation including structured active play) Model—for organizing physical rehabilitation sessions based on structured active play for preschoolers with cancer. The theory and empirically based model combine knowledge of early childhood development, play, physical activity and rehabilitation for children with cancer, and cancer treatment. With this model, we propose how to structure rehabilitation sessions, including goal-oriented, age-sensitive, fun movement activities that teach facilitate preschoolers to develop gross motor skills while enhancing their social and personal skills, through four core principles: 1) ritual practices, 2) reinforcement of movement through repetition, 3) development through appropriate challenge, and 4) adjusting activities to accommodate treatment-related side effects. This model holds promise for use with preschoolers diagnosed with cancer, as it is scalable and pragmatic and accounts for the children’s fluctuating physical capacity and daily well-being during cancer treatment.